Accuracy of Ultrasound for the Prediction of Placenta Accreta. Issue 3 (September 2015) - Bowman, Z.S.; Eller, A.G.; Kennedy, A.M.; Richards, D.S.; Winter, T.C.; Woodward, P.J.; Silver, R.M.
Abstract : ( Am J Obstet Gyneol . 2014;211:177.e1–177.e7)